Qur'anic Philosophical Foundations for Developing an Inclusive Islamic Religious Education Curriculum: Justice, Human Dignity, and Rahmatan lil 'Alamin - Muhammad Habibul Arif; Rani Rahmawati; Abdul Khobir; Moh. Mushlih (Research Journal on Teacher Professional Development, 2025)
Inclusive Islamic Religious Education (IRE) requires a robust Qur'anic philosophical foundation to transform the prevailing exclusive-doctrinaire paradigm into a humanistic, equitable, and transformative educational framework. This study aims to construct a Qur'an-based philosophical framework for developing an inclusive IRE curriculum grounded in three interconnected principles: justice (al-'adl), human dignity (karāmah insāniyah), and rahmatan lil 'ālamīn (mercy to all creation). The study adopts a qualitative approach using a library research design combined with the thematic tafsir (tafsir mawḍū'ī) method. Primary data comprise purposively selected Qur'anic verses representing the three philosophical principles, analyzed through four sequential stages: text identification, thematic categorization, philosophical interpretation, and pedagogical-curricular synthesis. The findings demonstrate that the three principles constitute an integrated philosophical trilogy in which justice serves as the structural foundation, human dignity as the ontological foundation, and rahmatan lil 'ālamīn as the axiological foundation of inclusive education. These principles are systematically derived from nine key Qur'anic verses: QS. An-Nahl [16]:90, QS. Al-Mā'idah [5]:8, and QS. An-Nisā' [4]:135 for justice; QS. Al-Ḥujurāt [49]:13, QS. Ar-Rūm [30]:22, and QS. Al-Isrā' [17]:70 for human dignity; and QS. Al-Anbiyā' [21]:107, QS. At-Taubah [9]:128, and QS. Āli 'Imrān [3]:159 for mercy. Their synthesis generates practical implications for five essential curriculum components: differentiated learning objectives, culturally responsive content, student-centered pedagogy, a dignified learning environment, and equitable assessment. This study contributes to Islamic educational philosophy by proposing an operational Qur'anic philosophical trilogy that bridges normative Qur'anic interpretation with practical curriculum development. It further offers a conceptual framework for curriculum developers, teachers, and policymakers to advance inclusive, context-sensitive, and transformative Islamic Religious Education while demonstrating the Qur'an's enduring epistemological relevance in addressing contemporary educational challenges